The Hera of Zeus Intimate Enemy, Ultimate Spouse - Pirenne-Delforge, Vinciane 1963- (Cambridge University Press, 2022)
Rethinks the workings of polytheism in ancient Greece through exploring the goddess Hera in her complex relationship to Zeus
Keywords: Hera-(Greek deity); Zeus-(Greek deity); Mythology, Greek; Electronic books